IMPLEMENTATION OF LEARNING CYCLE 7E MODEL TO PRACTICE METACOGNITIVE SKILLS ON REACTION RATE MATTER - Rosa, Dinda Diana; Azizah, Utiya (JCER (Journal of Chemistry Education Research), 2017)
The purpose of this research is to describe the implementation of Learning Cycle 7E modelsto practice students' metacognitive skills on reaction rate material at XI grade in SMAN 1 Taman. Theresearch instrument used is the implementation observationsheet of Learning Cycle 7E models,student activity sheet, test of metacognitive skill, and inventory metacognitive. The design of this studyis "One Shoot Case Study". The results of this study indicate: (1) the implementation of LearningCycle 7E models for four meetings are in good category and very good with an average value of 100;100; 100; 84,38; 62.50; 78,13; and 87.50; (2) Metacognitive skills of students on four meetingsobtained good and excellent criteria of planning skills of 3.19; 3.15; 3.41; and 3.48; monitoring skillsof 2.70; 3.19; 3.37; and 3.52; and evaluating skills at 2.30; 2.98; 3.32; and 3.61. (3) Metacognitiveskills of students based on metacognitive inventory are in good and excellent category with averagescore for four meetings: planning skills of 3.05; 3.12; 3.22; and 3.44; Monitoring skills of 3.04; 3.19;3.23; and 3.50: and evaluating skills 3.09; 3.17; 3.19; and 3.44.